Soil mapping by farmers in a Thai-Lao village in Northeast Thailand: A test of an ethnopedological research method - Yodda, Sujitra; Laohasiriwong, Suwit; Rambo, Terry (Forestry Faculty, Universitas Hasanuddin, 2022)
Having farmers draw soil maps of their communities has been frequently advocated as a faster, cheaper alternative to scientific soil surveying in developing countries. However, research on the extent to which farmers share common mental soil maps and the extent to which these match scientific maps is lacking. In this study, 11 Thai-Lao farmers were individually asked to draw maps showing the location of different types of soil in their village, and two groups of four farmers each were assembled to draw soil maps collectively. The maps were very different from each other and the extent to which they matched scientific categorizations of village soils was low. The maps of the individual farmers depicted two to five types of soil occupying two to seven zones. The map of one group depicted two types of soil in two zones, while the map of the other group depicted four types of soil in seven zones. When the soil zones on the maps drawn by the individual farmers were compared with scientific categorization of the soils at 26 sampling points, agreement was low, with an average of 11.6 full and partial matches. The performance of the group maps was not necessarily better: One group map had no full matches and only five partial matches while the other group map had 19 full and partial matches. In view of this heterogeneity in the soil knowledge of community members, ways must be found to identify the most knowledgeable farmers to draw the maps if farmer soil mapping is to be a useful research tool. This study found that the maps drawn by individuals who have had worked as hired laborers on plots in many parts of their village were generally more reliable than those drawn by farmers who had only worked on their own plots.